Evaluation of plyometric exercise training,weight training, and their combination on vertical jumping performance and leg strength - Fatouros, I. G.; Leontsini, D.; Taxildaris, K.; Aggeloussis, N.; Jamurtas, A. Z.; Kostopoulos, N.; Buckenmeyer, P. (The Journal of Strength and Conditioning Research, 2000)
The purpose of this study was to compare the effects of 3 different training protocols - plyometric training, weight training, and their combination - on selected parameters of vertical jump performance and leg strength. Forty-one men were randomly assigned to 1 of 4 groups: plyometric training (n = 11), weight training (n = 10), plyometric plus weight training (n = 10), and control (n = 10). Vertical jump, mechanical power, flight time, and maximal leg strength were measured before and after 12 weeks of training. Subjects in each training group trained 3 days per week, whereas control subjects did not participate in any training activity. Data were analyzed by a 2-way (4 × 2) analysis of variance (repeated-measures design). Results showed that all training treatments elicited significant (p < 0.05) improvement in all tested variables. However, the combination training group produced improvements in vertical jump performance and leg strength that were significantly greater than improvements in the other 2 training groups (plyometric training and weight training). This study provides support for the use of a combination of traditional and Olympic-style weightlifting exercises and plyometric drills to improve vertical jumping ability and explosive performance in general.